Of saints and blood: the Narita Buddhist sword cult in Edo Japan. (22nd May 2014) - Bond, Kevin
Abstract: This article examines the local character of early modern (1600–1868) Japanese Buddhism using a case study of the Narita Fudō cult of Shinshōji Temple, with particular attention to the temple's most sacred treasure, the legendary Sword of Amakuni. Drawing on local sources produced within and beyond clerical circles, it examines how the sword and its popular narratives became central to the public identity of the cult and the temple's proselytization efforts. This article illuminates the evolving, fluid nature of deity cults as highly mobile properties working across sectarian boundaries, and how these properties gained importance beyond the walls of Buddhist institutions among the artistic and theatrical landscapes of the country's capital.